Mediating effects of social support, mental health between stress overload, fatigue and turnover intention among operating theatre nurses - Jia-Bin Xu; Qing-Xiang Zheng; Xiu-Min Jiang; Qing Zhuo; Jin-Xia Nian; Jie-Ting Wang (BMC, 2023)
Abstract Background The high rate of nurses turnover and nursing staff shortage have been an ongoing concern issue and a challenge for global health systems. To explore the turnover intention among operating theatre nurses, and to test the hypothetical model for estimating the effects of stress overload and fatigue between social support, mental health and turnover intention. Design a multi-center and cross-sectional online survey. Methods This study was conducted from October 2020 to March 2021 comprised 1060 operating theatre nurses from 76 Chinese hospitals. The descriptive analysis, independent sample t test and one-way analysis of variance and Spearman correlation analysis were used to explore the relationships among variables by the SPSS software, and stepwise multiple linear regression analysis was utilized to identify influencing factors of turnover intention and its dimensions among operating theatre nurses. A structural equation model was analyzed by the AMOS software. Results Social support, mental health, stress overload and fatigue were important predictors of turnover intention among operating theatre nurses. Besides, stress overload positively affected fatigue, mental health and turnover intention; fatigue negatively affected social support, however, fatigue positively affected mental health; social support negatively affected mental health and turnover intention; mental health positively affected turnover intention. Moreover, social support, mental health mediated between stress overload, fatigue and turnover intention among operating theatre nurses. Conclusion Social support, mental health mediated between stress overload, fatigue and turnover intention among operating theatre nurses.